Aflibercept plus FOLFIRI in Asian patients with pretreated metastatic colorectal cancer: a randomized Phase III study. (17th August 2018) - Li, Jin; Xu, Ruihua; Qin, Shukui; Liu, Tianshu; Pan, Hongming; Xu, Jianming; Bi, Feng; Lim, Robert; Zhang, Suzhan; Ba, Yi; Bai, Yuxian; Fan, Nanfeng; et al.
Aim: To investigate whether the benefit of combining aflibercept with 5-fluorouracil, folinic acid and irinotecan (FOLFIRI) chemotherapy could be confirmed in patients from the Asia-Pacific region (ClinicalTrials.gov: NCT01661270). Patients & methods: Asian patients with oxaliplatin-pretreated metastatic colorectal cancer were randomized to receive aflibercept or placebo, followed by FOLFIRI. The primary end point was progression-free survival.Results: The intention-to-treat population comprised 332 patients. A clinical supply misallocation resulted in 198/332 (60%) patients receiving at least one cycle of misallocated treatment. Nevertheless, the addition of aflibercept to FOLFIRI was shown to improve progression-free survival (hazard ratio: 0.629; 95% CI: 0.488–0.812). Adverse events were in line with expectations.Conclusion: The beneficial treatment effect associated with the addition of aflibercept to FOLFIRI was confirmed in Asian patients with pretreated metastatic colorectal cancer. Lay Abstract: The Phase III VELOUR study showed that the addition of aflibercept to FOLFIRI chemotherapy significantly improved outcome in a predominantly western population of patients with metastatic colorectal cancer (mCRC), who had failed prior oxaliplatin-containing therapy. This Phase III study confirmed the aflibercept treatment effect and benefit in patients from the Asia-Pacific region with oxaliplatin-pretreated mCRC.